2016
DOI: 10.3389/fmicb.2016.01490
|View full text |Cite
|
Sign up to set email alerts
|

The Highly Conserved Escherichia coli Transcription Factor YhaJ Regulates Aromatic Compound Degradation

Abstract: The aromatic compound 2,4-dinitrotoluene (DNT), a common impurity in 2,4,6-trinitrotoluene (TNT) production, has been suggested as a tracer for the presence of TNT-based landmines due to its stability and high volatility. We have previously described an Escherichia coli bioreporter capable of detecting the presence of DNT vapors, harboring a fusion of the yqjF gene promoter to a reporter element. However, the DNT metabolite which is the direct inducer of yqjF, has not yet been identified, nor has the regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 25 publications
(36 reference statements)
2
22
0
Order By: Relevance
“…Daley et al (28), based on bioinformatics data, postulated that this gene encodes a transmembrane quinol oxidase subunit, which could explain the strong response of the yqjF-based reporter toward quinol and its derivatives, including THT. This is supported by recent findings regarding the regulatory protein YhaJ, which regulates the expression of yqjF and several other genes, all related to the biotransformation of quinol-like compounds (29). While this may suggest a possible role of YqjF in the downstream transformation of THT, a deletion of yqjF did not result in any significant effect on the yqjF::lux reporter's response toward DNT (our unpublished data).…”
Section: Discussionsupporting
confidence: 86%
“…Daley et al (28), based on bioinformatics data, postulated that this gene encodes a transmembrane quinol oxidase subunit, which could explain the strong response of the yqjF-based reporter toward quinol and its derivatives, including THT. This is supported by recent findings regarding the regulatory protein YhaJ, which regulates the expression of yqjF and several other genes, all related to the biotransformation of quinol-like compounds (29). While this may suggest a possible role of YqjF in the downstream transformation of THT, a deletion of yqjF did not result in any significant effect on the yqjF::lux reporter's response toward DNT (our unpublished data).…”
Section: Discussionsupporting
confidence: 86%
“…S6). These data correlate well with the RNA-seq analysis in identifying directly regulated targets such as several virulence factors, the GAD acid tolerance response, and the known target yqjF (24).…”
Section: Resultssupporting
confidence: 72%
“…1 B ). Most significantly, the down-regulation of virulence coincided with the up-regulation of several genes of the GAD acid fitness network ( P = 6.16 × 10 −7 ) and differential expression of the known YhaJ target gene yqjF (24).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…To confirm this phenomenon, we analyzed a known YhaJ target gene, yqjF, and similarly found that occupancy was not conditionally dependent or driven by YhaJ expression (see Fig. S1 in the supplemental material) (18). These results collectively indicate that differences in YhaJ enrichment at conserved sites are not exclusively driven by unexpected variations in TF dosage between members of the same species.…”
mentioning
confidence: 70%